Recuperação do cálcio contido em resíduos de incubatório por meio de tratamentos ácidos - Bugatti, Ederson Pastor (2016)
The generation of hatchery waste has been following the significant increase in poultry activity in Brazil. Due to this waste being aggressive to handle and of difficult recovery of nutrients, especially calcium, chemical treatments may be the solution. This study aimed to assess the feasibility of calcium recovery contained in hatchery waste through reaction with phosphoric and nitric acids in different concentrations. Besides the yield in calcium solubilization, pH and electric conductivity of the liquid fraction from the reaction were determined, as well as the yield of final product derived from lyophilization, probably dicalcium phosphate and calcium nitrate, both products of agronomic, nutritional, and commercial values. The most interesting results considering the yield of calcium solubilization were obtained using phosphoric acid in higher concentrations, i.e. 100 and 90%, namely 84.8 and 78.8%. For the nitric acid, the highest yields were obtained at concentrations of 100, 90, and 80%, with average scores of 72.2, 71.6, and 68.5% respectively. The yield of salt from the reaction with the acid was 2.5 and 2.4 tons of dicalcium phosphate per ton of waste hatchery (dry weight) and 2.0, 1.8 and 1.7 tons of calcium nitrate by tons of hatchery waste (dry mass). It was concluded that phosphoric acid at 100% was more efficient in the recovery of calcium contained in the hatchery waste, although nitric acid promotes further degradation of other components of hatchery waste, which generates a liquid fraction with higher electrical conductivity.